Design and modeling of pulsed-laser three-dimensional imaging system inspired by compound and human hybrid eye. Issue 1 (December 2018) - Cheng, Yang; Cao, Jie; Zhang, Fanghua; Hao, Qun
Abstract A pulsed-laser three-dimensional imaging system inspired by compound and human hybrid eye is proposed. A diffractive optical element is used to enlarge field of view (FOV) of transmitting system and a receiving system consisting of a non-uniform microlens array, an aperture array, and an avalanche photodiode array is designed. The non-uniform microlens array is arranged on a curved surface to mimic large FOV feature of the compound eye. Meanwhile, the non-uniform microlens array is modeled to mimic space-variant resolution property of the human eye. On the basis of the proposed system, some simulation experiments are carried out. Results show that the entire FOV is up to 52°, and the resolution is 30 × 18. The proposed system has a high resolution in the center FOV and a low resolution in the peripheral FOV. The rotation and scaling invariances of the human eye are verified on the proposed system. The signal-to-noise ratio (SNR) increases with the increase in the number of rings and the maximum SNR locates at the outmost periphery area. This work is beneficial to the design of the pulsed laser three-dimensional imaging system with large FOV, high speed, and high resolution.